Immunophenotyping of HPV Types 16 and 18 among Sudanese Patients with Oral Lesions - Ibrahim A. M. Ginawi; Ebtihag A. Mahgoub; Hussain G. Ahmed (Oman Medical Journal, 2012)
Objective: The aim of this study was to screen patients with oral lesions for the presence of Human Papilloma Virus (HPV) types 16 and 18.Methods: Sixty patients aged between 11-80 years with a mean age of 46 years were examined using immunohistological techniques. All samples were retrieved from RICK during the period from August 2009 to August 2010. Out of 60 patients, 50 had Oral Squamous Cell Carcinomas (OSCCs) and the remaining ten had benign oral lesions, included as internal control.Results: Of the 50 patients with OSCCs, 10 (20%) showed positive immunohistochemical results for HPV types 16 and 18 of which 50% were detected among males and 50% were demonstrated among females. The ten positive findings were Immunophenotyped as follows: five were positive with HPV type 16, four with type 18 and one was positive for HPV types 16 and18. All patients with benign oral lesions were negative for HPV immunohistochemistry.Conclusion: The study suggests the role of HPV 16 and 18 in the etiology of oral cancers in different parts of Sudan. However, the use of molecular techniques such as PCR are needed to confirm the results of immunohistochemistry in the role of the HPV in developing of OSCC in Sudan.